Coherent transition and diffraction radiation from a bunched 6.1MeV electron beam; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 227, Iss. 1-2 - Naumenko G. A. Gennadiy Andreevich; Aleinik A. N. Aleksandr Nikonorovich; Aryshev A. S.; Kalinin B. N.; Potylitsyn A. P. Alexander Petrovich; Saruev G. A. Gennady Alekseevich; Sharafutdinov A. F. (2005, 2005)
Title screen